Global coagulation assays in patients with multiple myeloma and monoclonal gammopathy of unknown significance. Issue 183 (November 2019) - Lim, Hui Yin; Brook, Rowena; Krishnamoorthi, Brintha; Tacey, Mark; Leung, Teresa; Donnan, Geoffrey; Nandurkar, Harshal; Ho, Prahlad
Highlights: Patients with plasma cell dyscrasia showed hypercoagulable thromboelastography. Peak thrombin was increased in patients with plasma cell dyscrasia. Patients with subsequent arterial thrombosis demonstrated hypofibrinolysis. There were no significant differences seen between patients with myeloma and MGUS. Global coagulation assays provide better coagulation assessment in these patients.